Exploring the Relationship between Social Norms and Pro-Environmental Attitudes in University Students: Implications for Environmental Education - Guido Ayay Arista; Alex Lenin Guivin Guadalupe; Jhon Angel Aguilar-Castillo; Jorge Antonio Malca Florindes; Francisco Martín Fernández Uceda; Mirta Margoth Julón Sánchez; Micaela Montenegro Arista (Migration Letters, 2023)
The purpose of this study was to investigate the relationship between social norms and pro-environmental attitudes in university students, as well as to explore the implications of these findings for environmental education. A total of 706 participants were recruited from three public universities in northern Peru by means of proportional stratified probability sampling, considering a confidence level of 95% and a margin of error of 3.5%. Both quantitative approach and correlational research designs were used. Data were collected using structured questionnaire-type scales that assessed students’ social norms and pro-environmental attitudes. The results show a positive relationship both moderate and significant between social norms and pro-environmental attitudes (Rs=0.268, p=0.000*<0.05). In addition, socio-demographic characteristics such as gender, age, academic cycle and area of knowledge were observed to have no significant impact on pro-environmental attitudes, while the factor institution and place of residence did influence this variable. In conclusion, this study sheds light on the relationship between social norms and pro-environmental attitudes in university students. It highlights the importance of considering social norms as part of environmental education programs in order to encourage more sustainable behavior and thus contribute to environmental conservation. These findings provide a solid basis for the implementation of effective strategies in the education of citizens committed to environmental conservation in this particular university context.